Improving Glycemic Safety in Non-ICU Wards With Continuous Glucose Monitoring - Jay Rajiv Shinde; Nikki Bharat Agarwal; Priyal Gangwar; Dhruv Manojkumar Jhawar (International Journal of Health Sciences and Research, 2026)
Continuous glucose monitoring (CGM) is increasingly being evaluated as an adjunct to point-of-care (POC) glucose testing in non-intensive care unit (non-ICU) hospital wards. Unlike intermittent POC measurements, CGM provides serial interstitial-glucose measurements and trend information that may reveal otherwise unrecognized glycaemic excursions. This narrative review critically synthesizes evidence from randomized controlled trials (RCTs), observational studies, systematic reviews and meta-analyses, clinical practice guidelines, and consensus statements, with emphasis on clinical effectiveness, analytical performance, safety, implementation, workflow, and economic considerations. The literature search covered PubMed/MEDLINE, Embase, and the Cochrane Library for publications from January 2010 through 31 May 2025. The review was intentionally narrative because the evidence base is heterogeneous with respect to study design, patient populations, CGM devices, comparators, insulin protocols, and outcome definitions; quantitative pooling was therefore not undertaken in this review. A recent systematic review and meta-analysis identified six RCTs involving 979 non-critically ill hospitalized adults with diabetes. Compared with POC testing alone, adding CGM increased time in range by 7.24 percentage points (95% CI 5.06–9.42), reduced time below 70 mg/dL by 1.23 percentage points (95% CI −2.27 to −0.18), reduced time below 54 mg/dL by 0.95 percentage points (95% CI −1.19 to −0.70), and reduced time above 250 mg/dL by 3.70 percentage points (95% CI −6.10 to −1.29); no significant differences were observed in glycaemic variability or insulin dose. [13] Across individual RCTs, CGM-assisted management generally improves glycaemic metrics and detection of hypo- and hyperglycaemia, whereas observational studies primarily support feasibility, workflow integration, and event detection. Current guidelines and consensus statements support inpatient CGM only within defined institutional protocols and with confirmatory POC testing when clinically indicated. Evidence for patient-centred outcomes such as length of stay, readmission, mortality, and cost-effectiveness remains limited. Analytical performance also varies by device and clinical context, and evidence does not justify a universal inpatient MARD threshold. Overall, CGM should be regarded as an adjunct—not a replacement—for POC glucose monitoring in appropriately selected non-ICU adults. Its greatest current value is continuous surveillance and trend information, while its routine use should remain contingent on patient selection, staff competency, institutional protocols, interoperability, and local regulatory and economic considerations. Larger pragmatic multicentre trials and standardized economic evaluations are needed before broader routine adoption can be recommended. Key words: Continuous glucose monitoring, diabetes, glycemic safety, hypoglycemia, hyperglycemia,